Does stretch training induce muscle hypertrophy in humans? A review of the literature. (5th February 2020) - Nunes, João Pedro; Schoenfeld, Brad J.; Nakamura, Masatoshi; Ribeiro, Alex S.; Cunha, Paolo M.; Cyrino, Edilson S.
Abstract: Stretch training is widely used in a variety of fitness‐related capacities such as increasing joint range of motion, preventing contractures and alleviating injuries. Moreover, some researches indicate that stretch training may induce muscle hypertrophy; however, studies on the topic have been primarily relegated to animal and in vitro models. The purpose of this brief review was to evaluate whether stretch training is a viable strategy to induce muscle hypertrophy in humans. An extensive literature search was performed using PubMed/MEDLINE, SciELO and Scopus databases, using terms related to stretching and muscle hypertrophy. Only human trials that evaluated changes in measures of muscle size or architecture following training protocols that it was performed stretching exercises were selected for inclusion. Of the 10 studies identified, 3 observed some significantly positive effects of stretch training on muscle structure. Intriguingly, in these studies, the stretching was carried out with an apparatus that aided in its performance, or with an external overload. In all studies, the subjects performed stretching at their own self‐determined range of motion, and no effect was observed. Of the 5 available studies that integrated stretching into a resistance training programme, 2 applied the stretching in the interset rest period and were the ones that showed enhanced muscle growth. In conclusion, passive, low‐intensity stretch does not appear to confer beneficial changes in muscle size and architecture; alternatively, albeit limited evidence suggests that when stretching is done with a certain degree of tensile strain (particularly when loaded, or added between active muscle contractions) may elicit muscle hypertrophy.